KEGIATAN PROGRAM KEMITRAAN MASYARAKAT DI SD MUHAMAMDIYAH PANDES BANTUL DENGAN KEGIATAN PENGHIJAUAN LINGKUNGAN SEKOLAH - Suseno, Hadi Prasetyo; -, Suraya; Fakiyah, Erfanti (Jurnal Pengabdi, 2019)
This paper examines the implementation of the community partnership program activities of the IST AKPRIND team in SD Muhammadiyah Pandes. One of the PKM activities is the greening program of the school environment. This goal is an effort to create an environmentally sound school. Current environmental issues are a serious problem that must be realized and must be delivered from the beginning to the younger generation, especially elementary students. A clean school environment is one element that must be developed and maintained continuously. In order for a comfortable education process it needs to be balanced with a healthy and clean environment. The implementation of PKM activities begins with a comparative study to partner locations and conducts surveys on school environment issues and the needs needed by schools, especially regarding environmental greening activities. PKM activities include reforesting the school environment as well as socializing the importance of a healthy environment and environmental issues for elementary school students. Activities involving students were provided with assistance in introducing environmental activities such as with coloring competitions with themes for students in grades 1 and 2, class hygiene competitions, installation of environment-themed posters. The results of the PkM activities are expected to make the school atmosphere more beautiful and students better understand the importance of cleanliness and maintenance of a beautiful and healthy school environment.